Basalt rock in sugarcane grown in ferralsols: changes in soil chemistry, mineralogy, and microbiology and in crop yield - Tarumoto, Miriam Büchler [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Since the sugarcane production mostly in highly weathered Brazilian soils, an alternative to increasing its yields, renewing these soils is required. Remineralization consists in add milled rock into the soils, as a soil conditioner, providing some minerals and elements. Besides the low cost, the consequences of their application are not totally elucidated. Therefore, the hypothesis of this study include the basalt rock dust treatment can improve the sugarcane yield, soil and plant chemical attributes; basalt rock dust increases the microbial index of soil quality; the rock application change microbial communities in the soil; and the rock weathering change the soil mineralogy. The aim of this study was evaluate the effects basalt rock dust application on sugarcane crops its consequences in soil mineralogy and microbiology. Despite not consistent to the four areas, basalt rock dust treatment can improve the sugarcane yield, soil chemical attributes, and microbial index of soil quality but a little is noticed in plant chemical attributes. The microbial diversity was not the same to the four areas, but it can be more related to geographical patterns than rock application, even with a little shift occurring, it cannot be attributed to the treatment. Weathering signals were noticed but there are two questionable points: the time to occur this weathering, may be quicker than it was thought, and the amount of weathered minerals. Basalt rock dust application improves sugarcane yield, it was notable its mineralogical changes in the soil and it does not cause damages to the soil microbial diversity. The microbial activity and footprints of soil microbiology in these conditions could elucidate the reason why occurred the yield improvement.
Rocha basáltica no cultivo de cana-de-açúcar em Latossolos: alterações na química, mineralogia e microbiologia de solo e na produtividade da cultura
Keywords: Saccharum spp.; Remineralization; Rocks for crops; Stalk yield; Soil microbiology; Soil minerals